"Sleep is for the weak" an in-depth analysis of why youths delay their bedtime - Chiam, Ting Wen (Nanyang Technological University, 2023)
There is an increasing number of youths who would sacrifice sleep in exchange for leisure time. This phenomenon has been dubbed ‘Revenge Bedtime Procrastination’ (RBP). Guided by the Social Model of Health and Socio-ecological Model of Health, this study investigates the social circumstances that lead to the prevalence of RBP among youths, how it differs among genders and how they manage its consequences. Data was gathered using focus group discussions and interviews with youths. Our findings revealed that youths procrastinate on their sleep due to their desire for leisure given their workload, their transitional stage in life, the culture of ‘working hard’ within the community and an inability to regulate their sleep cycle due to a sporadic schedule. This study seeks to deepen our understanding of RBP among youths so that effective interventions and messaging strategies can be designed to support youths in adopting healthier sleeping habits.